Assessment of different correlations to estimate distinct technology PV module operating temperature for Indian site. Issue 3 (29th March 2019) - Mohammed, Humaid; Gupta, Rajesh; Sastry, Oruganti; Magare, Dhiraj
Abstract: India is implementing one of the world's largest solar PV program. For better performance assessment of large PV installations, module temperature plays an important role. Estimation of power generation in hot climatic countries like India can be improved by the use of appropriate module temperature correlation. The accuracy of module temperature correlations has been observed to be related with climatic conditions. In this work, different explicit and implicit correlations have been evaluated in different temperature ranges based on frequency of occurrence of three very different technology PV modules: amorphous silicon, hetero‐junction intrinsic thin layer, and multicrystalline silicon at Indian site. Results show that Faiman correlation is most efficacious for all technology PV modules under highest frequency of occurrence temperature range. It has been observed that accuracy of correlations decreases from low module temperature range toward high module temperature range for all technology PV modules, except in case of Faiman correlation. In case of multicrystalline silicon, which is most widely used technology, the variation in accuracy of correlations was highest. This frequency of occurrence‐based comparison of correlation's accuracy is efficient and beneficial for better performance assessment of PV systems, especially in Indian context due to its large solar mission. Abstract : In this work, assessment of different explicit and implicit correlations for photovoltaic module temperature estimation has been presented for India, under low, mid, and high temperature ranges, based on the frequency of occurrence. Effectiveness of correlations for different technology photovoltaic modules has been compared under different temperature ranges and most suitable correlation has been obtained. This work can help in better assessment of PV system's field performance by using appropriate module temperature correlation.